The Effectiveness of Group Counseling with Self-Talk technique to Improve Students’ Self-Confidence - Tasdih, Tasdih; Japar, Muhammad; Awalya, Awalya (Jurnal Bimbingan Konseling, 2020)
Self confidence is important for every individual in order to have prosperity in lilfe. One that lacks self-confidence tends to feel dissatisfied with with himself and easy to give up. In relation to adolescents, they will gain negative impacts if they have got no strong self-confidence. Therefore, this study aimed at analyzing the effectiveness of group counseling with self-talk technique to improve students’ self-confidence. It used pretest and multiple posttest design. Purposive sampling was used to choose 16 experimental subjects placed into two groups, namely experimental group and control group with each group consisted of eight students. Their data were collected using self-confidence scale. According to the results of mixed repeated measures ANOVA, the group counseling with self-talk technique was effective to improve students’ self-confidence indicated by the value of (F (1.09)=2253.85, p < 0.05). These findings comfirm that group counseling with self-talk is able to improve students’ self-confidence.